Determinants affecting profitability of state-owned commercial banks: Case study of China - Ekaterina Koroleva; Shawuya Jigeer; Anqi Miao; Angi Skhvediani (Risks, 2021)
The study examines the relationship between internal determinants, external determinants and the profitability of state-owned commercial banks. We use pooled regression, fixed effect, and random effect models on the case of the top five Chinese state-owned commercial banks from 2007 to 2019. The results show that internal factors, measured by size, credit quality, and liquidity, significantly positively influence banks' profitability. State-owned banks that have larger sizes, higher credit quality, and higher liquidity have accordingly higher profitability than other banks. On the contrary, the external factor, measured by the natural logarithm of GDP, negatively influences banks' profitability. The decrease in GDP leads to higher profitability of state-owned commercial banks in China. Our results provide insight into the profitability of state-owned commercial banks, considering the latest changes in the Chinese banking industry.
Keywords: 330; Chinese state-owned commercial banks; credit quality; liquidity; profitability